Impact of suture mediated femoral access site closure with the Prostar XL compared to the ProGlide system on outcome in transfemoral aortic valve implantation. (15th November 2016) - Seeger, Julia; Gonska, Birgid; Rodewald, Christoph; Rottbauer, Wolfgang; Wöhrle, Jochen
Abstract: Background: Management of femoral access site is an important issue in transfemoral transcatheter aortic valve implantation (TAVI) and crucial for acute and long-term outcome. Data on vascular closure devices in this setting are limited. We evaluated safety and efficacy of the Prostar XL compared to the ProGlide suture-based vascular closure device. Methods and results: We enrolled 585 patients undergoing percutaneous transfemoral transcatheter aortic valve implantation (TAVI). Outcomes were defined according to Valve academic research consortium (VARC)-2 criteria. In 237 (40.5%) patients femoral access site closure was performed using the Prostar and in 348 patients (59.6%) using the ProGlide vascular closure device. There was no significant difference in patient baseline characteristics including single and dual antiplatelet therapies. Sheath outer diameter was significantly larger in the ProGlide compared with the Prostar group (7.7 ± 1.5 vs. 7.9 ± 0.5 mm; p = 0.001). Closure device failure according to VARC-2 criteria was significantly more frequent with the Prostar versus ProGlide device (19% vs. 4.6%; p < 0.01). Need for surgical repair (11.8% vs. 0%, p < 0.01), major (12.2% vs. 2.3%, p < 0.01) and minor (17.3% vs. 5.7%, p < 0.01) vascular complications and bleeding complications (5.5% vs. 2.0%, p = 0.02) occurred significantly more often with the Prostar device compared with the ProGlide system. In addition, in-hospital mortality was higher with Prostar compared with ProGlide (5.9% vs. 2.0%; p = 0.01). Conclusion: Femoral access site closure with the ProGlide device compared with the Prostar device in transfemoral aortic valve implantation was associated with significantly lower rates of closure device failure, minor and major bleedings and a significantly lower in-hospital mortality. Clinical Trial Registration: clinicaltrials.gov NCT02162069 .